Prevalence of Anemia among Working Pregnant Women and Their Pregnancy Outcome - Rahman, Matiur; Islam, Khaleda (RA Journal of Applied Research, 2023)
The main focus of this study was to discover prevalence of anemia among working pregnant women and their pregnancy outcome in Bangladesh. A cross-sectional observational study methodology and a multi-stage random sampling technique were chosen to select the study place. Estimated sample size was 410. A prepared and pre-tested questionnaire was used for data collection. Data was analyzed by Statistical Package for Social Sciences (SPSS) version 20. Both analytical and descriptive components were used for analysis. Chi-square test was used to find the association. The results were presented with some tabular form as well as in a descriptive manner. About three-fourth of the pregnancies resulted in normal pregnancy outcome, while 23.6% of the surveyed pregnant women experienced abnormal pregnancy outcomes i.e., preterm delivery (0.5%), low-birth weight baby (22.9%) and stillbirth (0.2%). Prevalence of anemia was 65.9%, with 45.4%, 19.8% and 0.5% of the women being mildly, moderately and severely anemic. Analysis reveals that abnormal pregnancy (i.e. Low birth weight, preterm delivery and still birth) outcomes were relatively higher among older mothers and women having lower level of educational qualifications. Severity of anemia during pregnancy had a statistically significant association with abnormal pregnancy outcomes (p=.000). Positive correlation was also found between monthly family income and weight of the baby which was statistically significant (p=0.011).